Scenarios for future Indian HFC demand compared to the Kigali Amendment. (1st July 2022) - Hillbrand, Alex; Madan, Prima; Singh, Manjeet; McNamara, Marie; Andersen, Stephen O; Mathur, Ajay; Shende, Rajendra; Jaiswal, Anjali
Abstract: Demand for hydrofluorocarbon (HFC) refrigerants used as substitutes for ozone-depleting substances is growing in India and is estimated to continue growing at a high rate through the middle of this century. HFCs, although not directly ozone-depleting, are highly potent greenhouse gases subject to a global phasedown under the 2016 Kigali Amendment to the Montreal Protocol on Substances that Deplete the Ozone Layer. As of 20 January 2022, 130 Parties have ratified the Kigali Amendment, including India. This analysis evaluates scenarios for India's HFC demand trajectory compared to likely control obligations under the Kigali Amendment. It is based on current and projected markets for HFC-using equipment and types of refrigerants utilized now and likely to be used in the future. Sectors considered in this work include mobile air conditioning, stationary air conditioning, refrigeration, and foam blowing agents. Results suggest that India's annual HFC demand under current market trends could reach 76 MMT CO2 -equivalent (CO2 e) in 2030 and 197 MMT CO2 e in 2050, from 23 MMT CO2 e in 2020, making no changes to the current mix of HFCs in use. The Kigali Amendment requires for compliance that India freeze its HFC consumption in 2028 at a projected level of 59–65 MMT CO2 e and phase down progressively over the following 29 years; in that case, annual Indian HFC demand would peak in 2030 at a projected 57 MMT CO2 e and fall to 8 MMT CO2 e by 2050. This trajectory would avoid cumulative HFC use of 2.2 GT CO2 e through 2050 versus the current market trends. If actions are taken to accelerate the refrigerant transition in stationary air conditioning by five years, India could peak its annual HFC demand by 2028 at 40 MMT CO2 e and avoid additional cumulative HFC demand of 337 MMT CO2 e between 2025 and 2050, exceeding its obligations under the Kigali Amendment.